Espalhamento inelástico de pósitrons por moléculas diatômicas - Pinheiro, Jenifer Geribola (2023)
The interaction between electrons and positrons with atoms and molecules has been the subject of extensive theoretical and experimental studies in recent years, as it enables advancements in understanding the dynamic interplay between these particles and matter. When addressing collisions between electrons and positrons with atomic or molecular targets, considering various interaction channels becomes crucial. These channels encompass not only elastic collisions but also excitation channels (electronic, vibrational, rovibrational), ionization, dissociation, and, in the case of positron projectiles, channels related to Positronium formation and annihilation. These two distinct characteristics of positron scattering introduce an additional challenge in the treatment of such systems, particularly from an experimental perspective and given the context of low energies. The experimental analysis, initiated in the 1970s, continues to face challenges, with persistent discrepancies in data. These disparities primarily arise from diculties in producing and controlling incident positron beams, especially at low energies. Theoretical challenges are equally prominent. The interaction between positrons and atomic or molecular targets is described through a positron-target potential that considers three regions: a short-range repulsive region, a long-range attractive region, and an intermediate region involving target correlation and polarization eects. The latter is undoubtedly the region that poses challenges for theorists. The eect of this interaction results from the modication of molecular/atomic charge due to the approach of the projectile and becomes more pronounced as the incident projectile energy decreases. In this context, we propose a theoretical computational approach to construct a potential energy surface (PES) for the interaction between positrons and diatomic molecules. This PES is parametrically dependent on the positron-target distance and, in principle, contains information about the three regions of interest. As a starting point, we employ the Finite Nuclear Mass Correction (FNMC) methodology, which treats the positron as a light nucleus. FNMC has been used in the treatment of positronic systems, particularly in constructing positron-atom interaction potentials with results comparable to the best available experimental data. In this study, we rene the methodology by applying it to positron-molecule systems. The PES is represented by an analytically adjusted function at ab-initio FNMC points, and this potential is used to compute elastic and inelastic cross-sections. The scattering equations are solved using the Close-Coupling (CC) approximation implemented in the computational code MOLSCAT. We apply our methodology to calculate cross-sections for elastic and inelastic scattering (rotational and vibrational) for positron-H2, N2, and O2 systems and compare them with recently reported experimental and theoretical data. As a result, we demonstrate that FNMC represents an alternative model to address the positron scattering problem in homonuclear diatomic molecules, yielding relevant insights into the mechanism of positron-molecule interaction, as electronic target structure information is computed in the PES. Moreover, the potential to obtain cross-sections for elastic and inelastic scattering, considering vibrational and rotational excitation channels using the same interaction potential, becomes highly appealing and applicable to numerous systems.